EFFECTS OF CLAMSHELL (Amusium Pleuronectes) CHITOSAN EXTRACT ON THE INCREASE NUMBER OF OSTEOBLAST OF THE ALVEOLAR BONE UNDER PERIODONTITIS - Rama Putranto; Muhamat Muhtar Safaat Abdurrohman; Cantika Ofintana Grati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Background: The number of patients with periodontal disease in Indonesia is estimated to continue to increase yearly. 4.79% or 34614 people had healthy periodontal tissue, while 95.21% or 687715 people had unhealthy periodontal tissue. Clamshell waste containing chitosan can be utilized, considering that interest in sources of raw materials derived from waste is increasing. Chitosan has a dual function, which is osteoinductive because it contains growth factors that provide growth for osteoblast cells.Methods: A true experimental laboratory study with a post-test-only control group design was conducted on 30 Wistar rats and divided into two groups: the 0.2% chlorhexidine gluconate group and the chitosan group of scallop shells (Amusium Pleuronectes). The increase in the number of osteoblasts was compared and analyzed.Results: The results showed that the average in the control group on days 7, 14, and 21 was 1, 3.20, 8.80, while in the treatment group on days 7, 14, and 21, it was 12.2, 21.8, and 25. Based on the One Way Anova test results, a p-value of 0,000 (p <0.05) was obtained, meaning a significant difference in the average number of osteoblast cells in each study group.Conclusion: This study concludes that there is an increasing effect of alveolar bone osteoblasts from chitosan in scallop shell extract (Amusium Pleuronecte) in Wistar rats with periodontitis.